2022
DOI: 10.5937/jaes0-35189
|View full text |Cite
|
Sign up to set email alerts
|

Optimization maintenance performance level through collaboration of overall equipment effectiveness and machine reliability

Abstract: Maintenance performance level (MPL) is an important part of the key performance indicator (KPI) to improve the effectiveness of machine maintenance which includes factors of overall equipment effectiveness-machine effectiveness (OEE-ME) and machine reliability (MR). The purpose of this paper is to optimize the value of the maintenance performance level (MPL) through the collaboration of overall equipment effectiveness-machine effectiveness (OEE-ME) and machine reliability (MR). The study began with collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The study found that an optimal maintenance time interval can meet the requirements for world-class maintenance performance, achieving an OEE value of 90.43%. Furthermore, the proposed machine reliability based on the FR value was superior to the initial machine reliability [25].…”
Section: The Benefits Of Applying Reliability-centred Maintenance To ...mentioning
confidence: 90%
See 1 more Smart Citation
“…The study found that an optimal maintenance time interval can meet the requirements for world-class maintenance performance, achieving an OEE value of 90.43%. Furthermore, the proposed machine reliability based on the FR value was superior to the initial machine reliability [25].…”
Section: The Benefits Of Applying Reliability-centred Maintenance To ...mentioning
confidence: 90%
“…These maintenance intervals are designed to achieve maximum performance in all departments while taking into account the potential for human errors during these activities [24]. Research conducted by Rahman et al, (2022) has confirmed that OEE is linked to increased machine reliability, and maximizing maintenance performance can significantly impact OEE. This approach involves analyzing data to determine the probability distribution of unplanned maintenance events and assessing machine reliability.…”
Section: The Benefits Of Applying Reliability-centred Maintenance To ...mentioning
confidence: 99%
“…In addition to these simple indicators, composite metrics are also used, including OEE (Overall Equipment Effectiveness), which is a combination of Availability, Performance, and Quality [39][40][41]. OEE is a measure of how well a manufacturing process is utilized compared to its full potential in ideal conditions, during the periods when it is scheduled to run.…”
Section: Introductionmentioning
confidence: 99%